Pengaruh Latihan Push Up dan Tricep Dips Terhadap Peningkatan Kekuatan Otot Lengan Atlet Bolavoli Putra Klub Perdana Wonosobo - Falih Akmal; Agung Wahyudi (Universitas Negeri Semarang, 2024)
This research aims to determine the effect of push up and tricep dips training on increasing arm muscle strength as well as the difference in the influence of push up and tricep dips training on increasing arm muscle strength of male volleyball athletes at the Perdana Wonosobo club. The method used is an experiment with a